2017
DOI: 10.3390/ijerph14121548
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Spontaneous Intracerebral Hemorrhage Cases between Urban and Rural Regions of Taiwan: Big Data Analytics of Government Open Data

Abstract: This study evaluated the differences in spontaneous intracerebral hemorrhage (sICH) between rural and urban areas of Taiwan with big data analysis. We used big data analytics and visualization tools to examine government open data, which included the residents’ health medical administrative data, economic status, educational status, and relevant information. The study subjects included sICH patients of Taipei region (29,741 cases) and Eastern Taiwan (4565 cases). The incidence of sICH per 100,000 population pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In this study, the surgical treatment rate of sICH inpatients was 30.84%, which was lower than that observed in northwest China (61.55%) [ 16 ] as well as in the United Kingdom (51.08%). [ 36 ] Our results indicated that the average hospital stay of sICH patients was 16 days, which was shorter than the 17.9 days observed in Taiwan [ 37 ] and longer than that observed in Canada (8 days). [ 38 ] In this study, the median cost of hospitalization was $3,608, which was lower than the $5,456 observed in Germany.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, the surgical treatment rate of sICH inpatients was 30.84%, which was lower than that observed in northwest China (61.55%) [ 16 ] as well as in the United Kingdom (51.08%). [ 36 ] Our results indicated that the average hospital stay of sICH patients was 16 days, which was shorter than the 17.9 days observed in Taiwan [ 37 ] and longer than that observed in Canada (8 days). [ 38 ] In this study, the median cost of hospitalization was $3,608, which was lower than the $5,456 observed in Germany.…”
Section: Discussionmentioning
confidence: 59%
“…Clinical decision support systems (CDSSs), which integrate electronic health records (EHRs) and expert knowledge, have improved the decision-making of physicians and medical caregivers [8][9][10][11]. Many methods have been developed for CDSSs, including linear/logistic regression, support vector machines (SVMs), decision trees, random forest (RF), rough sets, and trajectory methods [12][13][14][15][16][17][18]. Glycated hemoglobin (HbA1c) is extensively studied in these approaches because it is a good indicator of DM control.…”
Section: Introductionmentioning
confidence: 99%
“…15 16 17 18 Excellent scientific works have been published separately on the epidemiology, management, and clinical outcome of traumatic and nontraumatic ICH before. 5 11 13 19 20 21 22 23 24 25 26 However, the comparison of these populations based on data retrieved by different patient cohorts being treated at separate centers and disparate times is susceptible to a large amount of selection and treatment bias. To minimize the potential treatment bias, we directly compared patients with traumatic and nontraumatic ICH in a single cohort diagnosed and treated simultaneously in the same surgical department.…”
Section: Introductionmentioning
confidence: 99%